Response of the yield components and cultivation economics to Grow More Nutrition application on potato (Solanum Tuberosum L.) - Flieh, Sabah Abd Flieh; Idan, Razzaq Owayez; Abdullah, Kadum Mohammed Abdullah; Al-Ghazali, Noor A. (Journal of Kerbala for Agricultural Sciences, 2019)
This field experiment was coducted to evaluate the response of potato yield to foliar application of Grow More Nutrition. It was carried out in the vegetable research farm at the Department of Horticulture, Agriculture Collage, University of Karbala, Iraq during spring season 2015-2016. The treatments were three concentrations of Grow More Nutrition (T1 0 mg L-1 (control), T2 (25 mg L-1) and T3 (50 mg L-1) with three replication. The results showed that the application of T3 (50 mg L-1) had a sicnificant impact on number of tubers, tuber weight, yield per plant, total yield, net return and cost benefit ratio (8.67, 73.33, 0.64, 31.44 t ha-1, Din. 9408000 t.ha-1 And Din.3.969697 t ha-1, respectively.